Romania & Bulgaria 2026 - Baker, Mark (Travel writer); Busuttil, Shaun; Ragozin, Leonid; Suma, Monica (Lonely Planet guidebooks., 2026)
Lonely Planet's local travel experts reveal all you need to know to plan the trip of a lifetime in this latest edition of our guide to Romania & Bulgaria. Discover Romania & Bulgaria's most popular experiences and best kept secrets from sunning yourself on miles of golden sand at Sunny Beach; to sipping coffee and people watching from a rooftop bar in Bucharest; and exploring Corvin Castle, Transylvania's most spellbinding fortress.